2019
DOI: 10.1038/s41699-019-0087-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective control of molecule charge state on graphene using tip-induced electric field and nitrogen doping

Abstract: The combination of graphene with molecules offers promising opportunities to achieve new functionalities. In these hybrid structures, interfacial charge transfer plays a key role in the electronic properties and thus has to be understood and mastered. Using scanning tunneling microscopy and ab initio density functional theory calculations, we show that combining nitrogen doping of graphene with an electric field allows for a selective control of the charge state in a molecular layer on graphene. On pristine gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 42 publications
7
31
0
Order By: Relevance
“…This structure is stabilized by dipole-dipole interactions between the cyano endgroups and the quinone center of neighboring molecules. This assembly is very similar to typical self-assembled TCNQ islands on weakly interacting substrates [5,23,[47][48][49]. When measured at a lower bias voltage (e.g., at V = 0.2 V in Figure 4a), the molecules appear with featureless elliptical shape, reflecting only the topographic extent of the molecules.…”
Section: Electronic Properties Of Tcnq Molecules On Mos 2 On Ag(111)supporting
confidence: 66%
See 2 more Smart Citations
“…This structure is stabilized by dipole-dipole interactions between the cyano endgroups and the quinone center of neighboring molecules. This assembly is very similar to typical self-assembled TCNQ islands on weakly interacting substrates [5,23,[47][48][49]. When measured at a lower bias voltage (e.g., at V = 0.2 V in Figure 4a), the molecules appear with featureless elliptical shape, reflecting only the topographic extent of the molecules.…”
Section: Electronic Properties Of Tcnq Molecules On Mos 2 On Ag(111)supporting
confidence: 66%
“…For the identification of molecular orbitals, it is often sufficient to compare the d I /d V maps with the shape of the gas-phase molecular orbitals. Using this method, the U-shaped features have previously been associated to the LUMO of TCNQ [ 5 , 23 , 49 ]. Here, we corroborate this assignment by simulating constant-height d I /d V maps of a free, flat-lying molecule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations revealed that a local charge transfer occurs at the nitrogen site, so that the molecule gains 0.33 electron, as compared to 0.20 electron at carbon sites ( Fig. 10c and d) [74]. A combination of this effect with local gating allows to obtain a molecular layer with a mixed charge state.…”
Section: Molecular Interactionmentioning
confidence: 95%
“…This effect has been exploited to perform catalysis, or electrochemical sensing with nitrogen-doped graphene [2,71]. The electronic properties of molecules interacting with nitrogen sites has been investigated with scanning probe microscopy [61,[72][73][74]. STM experiments on free base tetraphenylporphyrin molecules (H 2 TPP) have shown that at nitrogen sites, the molecules undergo a downshift of their highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) states, evidencing a local charge transfer at these sites ( Fig.…”
Section: Molecular Interactionmentioning
confidence: 99%